Dissipationless transport signature of topological nodal lines - Arthur Veyrat; Klaus Koepernik; Louis Veyrat; Grigory Shipunov; Iryna Kovalchuk; Saicharan Aswartham; Jiang Qu; Ankit Kumar; Michele Ceccardi; Federico Caglieris; Nicolás Pérez; Romain Giraud; et al. (Nature Communications)
Abstract Topological materials, such as topological insulators or semimetals, usually not only reveal the non-trivial properties of their electronic wavefunctions through the appearance of stable boundary modes, but also through very specific electromagnetic responses. The anisotropic longitudinal magnetoresistance of Weyl semimetals, for instance, carries the signature of the chiral anomaly of Weyl fermions. However for topological nodal line semimetals—materials where the valence and conduction bands cross each other on one-dimensional curves in the three-dimensional Brillouin zone—such a characteristic has been lacking. Here we report the discovery of a peculiar charge transport effect generated by topological nodal lines in trigonal crystals: a dissipationless transverse signal in the presence of coplanar electric and magnetic fields, which we attribute to a Zeeman-induced conversion of topological nodal lines into Weyl nodes under infinitesimally small magnetic fields. We evidence this dissipationless topological response in trigonal PtBi2 persisting up to room temperature, consistent with the presence of extensive topological nodal lines in the band structure of this non-magnetic material. These findings provide a pathway to engineer Weyl nodes by arbitrary small magnetic fields and reveal that bulk topological nodal lines can exhibit non-dissipative transport properties.